2011
DOI: 10.1109/tsp.2011.2106780
|View full text |Cite
|
Sign up to set email alerts
|

Design of Robust Superdirective Arrays With a Tunable Tradeoff Between Directivity and Frequency-Invariance

Abstract: Frequency-invariant beam patterns are often required by systems using an array of sensors to process broadband signals. If the spatial aperture is shorter than the involved wavelengths, using a superdirective beamforming is essential to get an efficient system. In this context, robustness of array imperfections is a crucial feature. In the literature, only a few approaches have been proposed to design a robust, superdirective, frequency-invariant beamformer based on filter-and-sum architecture; all of them ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 19 publications
0
49
0
Order By: Relevance
“…In the foregoing example, the transformation matrix (17) takes on the following values− whose rows can be regarded as beamforming weighing windows with nominal looking directions π/2, ± arc cos(1/2.1), and ± arccos(2/2.1), respectively. Inspection of the values of the entries in (18), in particular of those with alternating signs in the first row (associated to the broadside direction), indicates that the array is being operated in super-directive conditions, with a degree of super-directivity depending on the choice of parameters involved in the extrapolation procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the foregoing example, the transformation matrix (17) takes on the following values− whose rows can be regarded as beamforming weighing windows with nominal looking directions π/2, ± arc cos(1/2.1), and ± arccos(2/2.1), respectively. Inspection of the values of the entries in (18), in particular of those with alternating signs in the first row (associated to the broadside direction), indicates that the array is being operated in super-directive conditions, with a degree of super-directivity depending on the choice of parameters involved in the extrapolation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting aspect that is worth pursuing relates to the properties of the beam patterns that are implicitly generated by the rows of the transformation matrix in (16) or (17). Actually, it can be shown that through a proper choice of the parameters M, Δ, and N, the number Q of these beams and their directivity can easily exceed those achievable through uniform-weighing beamforming applied to critically spaced arrays of equal length.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, as evident from earlier designs for superdirective narrowband arrays [12]- [16], broadband beamformers designed for physically-compact applications can likewise become very sensitive to errors in array imperfections and therefore robustness constraints need to be incorporated in the design [3,17]- [23]. In [17]- [21], the statistics of microphone characteristics are taken into account to derive broadband beamformers that are robust to microphone mismatches, while in [3,22,23] the white noise gain (WNG) is incorporated in the design to ensure that the beamformer is robust to spatial white noise and array imperfections. The use of the WNG constraint is not new and has been used in earlier beamformer designs to ensure robustness in superdirective beamformers [12]- [14].…”
Section: Introductionmentioning
confidence: 99%